College Students' Use of the Internet - Anna C. McFadden (Arizona State University, 1999)
Over the last several years there has been mounting concern about children being exposed to sex-related material on the Internet. Concern about pornography and obscenity is widespread and this concern has spawned a host of products to block or filter content. The notorious Time magazine article (July 3, 1995) "Cyberporn"--which Time later acknowledged had doubtful credibility (July 24, 1995)--undoubtedly inflamed this trend. The article, which asserted that much of traffic on the Internet dealt with pornography, was based on the largely discredited research of a Carnegie Mellon undergraduate student who examined 32 alt.binaries newsgroups on Usenet, not the Internet. Nonetheless, the article was fodder for the Communications Decency Act of 1996. While the Supreme Court struck down the Act, pending bills such as the "Safe Schools Internet Act" (H.R. 3177) would require all public libraries and schools that receive federal funds for Internet access to install blocking software to restrict minors' access to "inappropriate" material. Other pending bills would punish commercial online distributors for access to material they do not directly control and require service providers to offer blocking software to customers. While most students who use computers in university computer labs are legally adults, many are not. If laws restrict access to minors, there will be a host of technical problems to provide access to scholars and adult students. Labs are open spaces where students come and go, using computers for many purposes but only part of the time for Internet access. Determining policies and creating procedures to implement and monitor policies will entail considerable resources for something that may not be a serious problem and something that cannot be effectively controlled with filtering software. It could require students to present identification to prove they are adults in order to access certain computer resources, not to mention the procedures that would be used to restrict access to those who are minors. There is no way to verify age on the Internet, so the responsibility would fall to the school staff. For the time being, most universities have policies that limit computer use to legitimate educational purposes, and students in most universities have mainly unrestricted access. There is little or no information about how the Internet is used in such settings.